2021
DOI: 10.30684/etj.v39i2a.1743
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition of Composite Motions based on EMG Signal via Machine Learning

Abstract: In the past few years, physical therapy plays a crucial role during rehabilitation. Numerous efforts are made to demonstrate the effectiveness of medical/ clinical and human-machine interface (HMI) applications. One of the most common control methods is using electromyography (EMG) signals generated by muscle contractions to implement the prosthetic human body parts. This paper presents an EMG signal classification system based on the EMG signal. The data is collected from biceps and triceps muscles for six di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The algorithms of NN are typically much faster than those of conventional iterative CF techniques. Additionally, the solution does not require an initial guess, and there is an ability to implement the designed network model with special-purpose hardware and, in this way, take advantage of the full ability of NN, including high processing speed [17][18][19][20].…”
Section: Fast Curve Fitting Using Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithms of NN are typically much faster than those of conventional iterative CF techniques. Additionally, the solution does not require an initial guess, and there is an ability to implement the designed network model with special-purpose hardware and, in this way, take advantage of the full ability of NN, including high processing speed [17][18][19][20].…”
Section: Fast Curve Fitting Using Neural Networkmentioning
confidence: 99%
“…This suggested approach is implemented using the principle of fast processing Curve Fitting (CF) executed by Neural Networks (NNs). NNs have been employed in various fields due to, in part, a new powerful algorithm development that affects their ability to process information rapidly and leads to faster response [17][18][19][20]. NNs provide a perfect tool with high accuracy and fast response solution for nonlinear CF problems [15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the training phase of KNN saves the training set feature vectors with their related class labels. In the testing phase, the algorithm determines the K value, which can be estimated by trial and error and find out the optimal K value like 2,3 or 5, or it can be identified based on the dataset by using the following equation [14,15,16]:…”
Section: K-nearest Neighbor (Knn) Classifiermentioning
confidence: 99%